Incidence, mortality and outcome of meningiomas: A population-based study from Germany - Holleczek, Bernd; Sahm, Felix; Deimling, Andreas von (Cancer epidemiology, 2019)
Background - Meningiomas are mostly benign tumors that originate from the coverings of the brain and spinal cord. Compared to malignant glial tumors, meningiomas are relatively understudied with regard to their risk factors and epidemiology. In particular, population-based data on cancer burden and patient outcomes are scant. - Methods - Population-based data from Saarland, a federal state in South-Western Germany, were used; the data included 992 patients diagnosed with a first meningioma between 2000 and 2015. Incidence and mortality rates—as well as estimates of observed and relative survival and cumulative incidence of tumor recurrence up to 10 years after diagnosis—were derived by sex, age, WHO grade, and whether or not the patient had undergone surgery. - Results - This population-based study not only included patients treated in the regional university hospital but also those treated elsewhere or patients without any surgical treatment. The mean age of the patients at diagnosis was 63 years, and 70%, 28% and 3% had WHO grade I, II and III meningiomas, respectively. Ten-year observed and relative survival of all patients combined was 72% and 91% respectively. Tumor-related mortality varied by sex and increased with age at diagnosis and the WHO grade of the tumor. The overall 10-year cumulative incidence of meningioma recurrence was 9%. - Conclusion - This analysis represents the first modern population-based analysis of meningioma incidence and mortality and outcomes of patients with such neoplasms in Germany. Derived from an unselected sample of patients, this study may fill a hitherto existing gap in the literature on meningiomas.
Gesehen am 10.12.2019